Misfit Dislocation Guided Topographic and Conduction Patterning in Complex Oxide Epitaxial Thin Films. Issue 14 (13th April 2016) - Sandiumenge, Felip; Bagués, Núria; Santiso, José; Paradinas, Markos; Pomar, Alberto; Konstantinovic, Zorica; Ocal, Carmen; Balcells, Lluís; Casanove, Marie‐Jo; Martínez, Benjamín
Abstract : Interfacial dissimilarity has emerged in recent years as the cornerstone of emergent interfacial phenomena, while enabling the control of electrical transport and magnetic behavior of complex oxide epitaxial films. As a step further toward the lateral miniaturization of functional nanostructures, this work uncovers the role of misfit dislocations in creating periodic surface strain patterns that can be efficiently used to control the spatial modulation of mass transport phenomena and bandwidth‐dependent properties on a ≈20 nm length scale. The spontaneous formation of surface strain‐relief patterns in La0.7 Sr0.3 MnO3 /LaAlO3 films results in lateral periodic modulations of the surface chemical potential and tetragonal distortion, controlling the spatial distribution of preferential nucleation sites and the bandwidth of the epilayer, respectively. These results provide insights into the spontaneous formation of strain‐driven ordered surface patterns, topographic and functional, during the growth of complex oxide heterostructures on lengths scales far below the limits achievable through top‐down approaches. Abstract : Misfit dislocations in La0.7 Sr0.3 MnO3 /LaAlO3 compressively strained heterostructures are shown to induce topographic and surface current patterning. The underpinning mechanism of this behavior is a lateral modulation of surface strain influencing the chemical potential (Δ μ ) and the bandwidth ( W ) at the free surface, providing a clue for the realization of spontaneous functional nanostructures in the ≈20 nm range.